The Systemic Alterations of Lipids, Alanine-Glucose Cycle and Inter-Organ Amino Acid Metabolism in Swine Model Confirms the Role of Liver in Early Phase of Septic Shock - Ferrario, Manuela; Brunelli, Laura; Su, Fuhong; Herpain, Antoine; Pastorelli, Roberta (Frontiers in Physiology, 2019)
Septic shock is a medical emergency and is one of the main causes of mortality in critically ill patients. Given the pathophysiological complexity of sepsis spectrum and progression in clinical settings, animal models become essential tools to improve patient care and to understand key mechanisms that may remain masked from the heterogeneity of clinical practice. Our aim was to verify whether the metabolic constellations we previously reported for septic shock patients appear also in our septic shock swine model as systemic markers of early disturbances in energy metabolism and hepatic homeostasis. Septic shock was induced in anesthetized, instrumented and ventilated adult swines by polymicrobial peritonitis. Hemodynamic and serial measurements of arterial and mixed venous blood gases were made. Laboratory measurements and mass spectrometry-based targeted quantitative plasma metabolomics were performed in blood samples collected at baseline, at shock and at fully resuscitation after fluids and vasopressors administration. Data elaboration was performed by multilevel and multivariate analysis. Changes in hemodynamic, blood chemistry and inflammatory markers were in line with a septic shock phenotype. Time course alteration of systemic metabolites were characterized by marked decreased in phosphatidylcholines and lysophosphatidylcholines species, altered alanine-glucose cycle and inter-organ amino acid metabolism, pointing toward an early hepatic impairment similarly to what we previously reported for septic shock. This is the first study in which an experimental swine model of septic shock recapitulates the main metabolic derangements reported in a clinical setting of shock. These events occur within hours from infections and may act as early metabolic features to assist in evaluating subclinical hepatic alterations and pave the way to improve the management of septic shock.